Penerapan Hukum Terhadap Tindak Pidana Pemalsuan Sertifikat Hak Atas Tanah di Labuan Bajo Kabupaten Manggarai Barat - Maria Inda Jelita; I Nyoman Sukandia; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2024)
Land ownership rights will continue as long as the owner is alive, and after death, the rights can be continued by their heirs provided they meet the criteria as subjects of ownership rights. Certificate forgery is a criminal act involving the deliberate act of making it appear genuine, although it is actually fake or deceptive. The case of land disputes in the forgery of land certificates in Labuan Bajo has its legal application. So that the formulation of the problem is how the legal arrangements against perpetrators of criminal acts of forgery of land rights certificates in Labuan Bajo, West Manggarai Regency and how the application of the law against perpetrators of criminal acts of forgery of land rights certificates in Labuan Bajo, West Manggarai Regency. Using empirical research methods. Based on the results of his research, legal regulations related to forgery of land rights certificates are regulated in Article 263 of the Criminal Code. Perpetrators of criminal acts can be reported to law enforcement and in the trial process, perpetrators of certificate forgery can be subject to imprisonment of between 6 months to 12 years.